Fasting metbabolism in Antarctic fur seal (Artocephalus gazella) pups - John Arnould; J Green; D Rawlins (2001)
The metabolism of 52–73-day old Antarctic fur seal pups from Bird Island, South Georgia, was investigated during fasting periods of normal duration while their mothers were at sea foraging. Body mass decreased exponentially with pups losing 3.5–3.8% of body mass per day. Resting metabolic rate also decreased exponentially from 172–197 ml (O2)·min −1 at the beginning of the fast and scaled to M b 0.74 at 2.3 times the level predicted for adult terrestrial mammals of similar size. While there was no significant sex difference in RMR, female pups had significantly higher ( F 1 , 18 =6.614, P <0.019) mass-specific RMR than male pups throughout the fasting period. Fasting FMR was also significantly ( t 15 =2.37, P <0.035) greater in females (823 kJ·kg −1 ·d −1 ) than males (686 kJ·kg −1 ·d −1 ). Average protein turnover during the study period was 19.3 g·d −1 and contributed to 5.4% of total energy expenditure, indicating the adoption of a protein-sparing strategy with a reliance on primarily lipid catabolism for metabolic energy. This is supported by observed decreases in plasma BUN, U/C, glucose and triglyceride concentrations, and an increase in β-HBA concentration, indicating that Antarctic fur seals pups adopt this strategy within 2–3 days of fasting. Mean RQ also decreased from 0.77 to 0.72 within 3 days of fasting, further supporting a rapid commencement of protein-sparing. However, RQ gradually increased thereafter to 0.77, suggesting a resumption of protein catabolism which was not substantiated by changes in plasma metabolites. Female pups had higher TBL (%) than males for any given mass, which is consistent with previous findings in this and other fur seal species, and suggests sex differences in metabolic fuel use. The observed changes in plasma metabolites and protein turnover, however, do not support this.